2006
DOI: 10.1146/annurev.biochem.75.103004.142443
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide Reductases

Abstract: Ribonucleotide reductases (RNRs) transform RNA building blocks to DNA building blocks by catalyzing the substitution of the 2'OH-group of a ribonucleotide with a hydrogen by a mechanism involving protein radicals. Three classes of RNRs employ different mechanisms for the generation of the protein radical. Recent structural studies of members from each class have led to a deeper understanding of their catalytic mechanism and allosteric regulation by nucleoside triphosphates. The main emphasis of this review is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
1,209
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 984 publications
(1,224 citation statements)
references
References 148 publications
12
1,209
0
3
Order By: Relevance
“…It catalyzes the reduction of ribonucleotides (nucleoside triphosphates [NTPs]) to their corresponding 2=-deoxyribonucleotides (deoxynucleoside triphosphates [dNTPs]) and therefore plays an essential role in DNA synthesis and repair. Three RNR classes (classes I, II, and III) exist; these classes exhibit different primary structures, subunit cofactor requirements, and quaternary three-dimensional (3D) structures, but they all are allosterically regulated and share similar catalytic mechanisms (1,2). Class I RNRs are oxygendependent enzymes that occur in eubacteria, eukaryotes, and some viruses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It catalyzes the reduction of ribonucleotides (nucleoside triphosphates [NTPs]) to their corresponding 2=-deoxyribonucleotides (deoxynucleoside triphosphates [dNTPs]) and therefore plays an essential role in DNA synthesis and repair. Three RNR classes (classes I, II, and III) exist; these classes exhibit different primary structures, subunit cofactor requirements, and quaternary three-dimensional (3D) structures, but they all are allosterically regulated and share similar catalytic mechanisms (1,2). Class I RNRs are oxygendependent enzymes that occur in eubacteria, eukaryotes, and some viruses.…”
mentioning
confidence: 99%
“…nrdD and nrdG form an operon and encode the catalytic NrdD subunit and the activating protein NrdG, respectively. This system works only under strict anaerobic conditions because oxygen is toxic to these enzymes (1,2). Notably, the distribution of the different RNR classes is difficult to elucidate, as the different bacterial phylogenetic groups do not display any common RNR combinations.…”
mentioning
confidence: 99%
“…R2 is rate limiting for the enzymatic activity of RNR and its level is cell cycle dependent (Chabes and Thelander, 2000). However, an analogue of R2, p53R2 has recently been found that is not cell cycle dependent (Guittet et al, 2001;Nordlund and Reichard, 2006). p53R2 can substitute for R2 to form an active RNR enzyme capable of generating deoxyribonucleotides in resting cells or following DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…9 While the R1 subunit is expressed in quiescent cells, although at a low level, the R2 subunit expression is silenced. 10 Here, we report that HBV increases the dNTP pool for effective viral production in quiescent cells by directly targeting the R2 gene to induce unscheduled R2 expression without affecting cell cycle progression.…”
mentioning
confidence: 99%